Renewable Energy For Sustainable Development In Remote Areas Of India.. - A. Aziz, Shaikh Umer.; S. Pathak, Sudhanshu; R. Patil, Ashwini (Journal of Neonatal Surgery, 2025)
This study examines the potential of renewable energy (RE) systems to drive sustainable development in India’s remote and rural regions where conventional electrification remains challenging. It evaluates solar, biomass, and micro-hydropower technologies for their technical feasibility, cost-effectiveness, and socio-economic benefits. Using secondary data, government reports, and three rural case studies, the research analyzes how decentralized RE systems can meet energy demands while promoting inclusive growth. The findings reveal that renewable technologies not only reduce dependency on fossil fuels but also enhance agricultural productivity, improve education and healthcare access, and generate local employment. Cost comparisons indicate that renewable projects are more economical than grid extensions, particularly in sparsely populated or geographically isolated areas. The study also benchmarks RE performance against national electrification goals under the Saubhagya Scheme, showing 99% electrification in RE-supported areas, surpassing the national average of 97%. Despite challenges such as high initial costs, bureaucratic delays, and technical maintenance issues, renewable energy adoption has proven vital in bridging the rural–urban energy divide. This research underscores the importance of decentralized RE systems in achieving sustainable energy security and meeting India’s Sustainable Development Goals (SDGs)...